Predicting plastron thermodynamic stability for underwater superhydrophobicity - Tesler, Alexander; Nurmi, Heikki A.; Kolle, Stefan; Prado, Lucia; Karunakaran, Bhuvaneshwari; Mazare, Anca Valentina; Erceg, Ina; de brito soares, Íris; Sarau, George; Christiansen, Silke; Stafslien, Shane; Alvarenga, Jack; et al. (Communications Materials, 2024)
Non-wettable surfaces, especially those capable of passively trapping air in rough protrusions, can provide surface resilience to the detrimental effects of wetting-related phenomena. However, the development of such superhydrophobic surfaces with a long-lasting entrapped air layer, called plastron, is hampered by the lack of evaluation criteria and methods that can unambiguously distinguish between stable and metastable Cassie-Baxter wetting regimes. The information to evaluate the stability of the wetting regime is missing from the commonly used contact angle goniometry. Therefore, it is necessary to determine which surface features can be used as a signature to identify thermodynamically stable plastron. Here, we describe a methodology for evaluating the thermodynamic underwater stability of the Cassie-Baxter wetting regime of superhydrophobic surfaces by measuring the surface roughness, solid-liquid area fraction, and Young’s contact angle. The method allowed the prediction of passive plastron stability for over one year of continuous submersion, the impeding of mussel and barnacle adhesion, and inhibition of metal corrosion in seawater. Such submersion-stable superhydrophobicity, in which water is repelled by a stable passive air layer trapped between the solid substrate and the surrounding liquid for extended periods at ambient conditions, opens new avenues for science and technologies that require continuous contact of solids with aqueous media. (Figure presented.).
CRIS-Team Scopus Importer:2024-07-12